Development of Hyperalgesia in Patients Treated with Autologous Platelet Rich Plasma Due to Androgenetic Alopecia - Yildirim, Mehmet; İnce, Bilsev; Uyanık, Orkun; Okur, Mehmet İhsan; Dadacı, Mehmet (My University, 2018)
Aim: Platelet-rich plasma (PRP) is thought to exerts its effect through the growth factors present inthe alpha granules of the platelets, depending on its high platelet concentration. The increasing feelingof pain in recurrent attempts raises the question that PRP may cause hyperalgesia associated withhypersensitization. There is no publication in the literature reporting peripheral sensitization caused byany recurrent injection of PRP. In this study, we aimed to investigate whether hyperalgesia occurs due tohypersensitization in PRP patients with androgenetic alopecia.Patients and Methods: Between 2016 and 2017, 10 male patients aged 25-35 years who had androgeneticalopecia were included in the study. Autologous PRP was injected intradermally as 1 mL per cm2 in thediseased frontal and parietal area of scalp, and then the injection was repeated at the first, second andsixth months. Patients’ responses to painful stimulus were investigated immediately before all injectionsand at the first year using Von Frey filaments in variable. Hyperalgesia scores of each measurement weredetermined by averaging results of the two surgeons. Patients who had hair loss were evaluated withdermoscopy. The number of hair follicles per unit area was detected and the patients’ photographs weretaken at each control.Results: The mean age of the participants was 29.4 years. When patients were evaluated for hyperalgesia,it was observed that after each PRP application, pain was felt with less amount of g stimulation comparedto before PRP injection (p <0.05). The highest period of hyperalgesia was in the first year after PRP (P<0.05). The increase in hair density was calculated as 6.4, 9.4, 21, and 27,6% at 1st, 2nd, 6th, and 12thmonths after the first treatment.Conclusion: We determined that hyperalgesia may occur in patients because of repeated PRP injections.The development of hyperalgesia in these patients may be due to growth factors in the PRP content.Further experimental and clinical studies are needed to determine the cause of hyperalgesia occurringafter repeated PRP injections.
Keywords: Dermatoloji; Genel ve Dahili Tıp; Androloji